Der Schutz personenbezogener Daten im Strafverfahren Eine rechtsvergleichende Untersuchung zum deutschen und US-amerikanischen Recht - Park, Sohyun (2021)
On the one hand, the fast processing speed and the storage and linking possibilities when dealing with electronic data make human life convenient and practical; on the other hand, however, they can also endanger people's lives of freedom. By combining it with other data, we are moving closer to becoming a transparent citizen. In the context of these challenges, the freedom of the individual is at stake. It is essential that personal data be evaluated with appropriate safeguards that adequately protect individuals against the unauthorized or excessive collection, storage, use and disclosure of data concerning them.